2010
DOI: 10.1097/eja.0b013e3283383506
|View full text |Cite
|
Sign up to set email alerts
|

N-Acetylcysteine does not prevent renal dysfunction after off-pump coronary artery bypass surgery

Abstract: N-Acetylcysteine does not have any beneficial effect on renal function in high-risk patients undergoing off-pump coronary artery bypass graft.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 28 publications
0
14
1
Order By: Relevance
“…Moreover, in this study, patients treated with N‐acetylcysteine were less likely to require mechanical ventilation for a prolonged (>48 hours) period (3% vs 18%; P < .001) and to have a stay in the intensive care unit of longer than 4 days (13% vs 33%; P < .001), suggesting a positive effect of N‐acetylcysteine on CPB‐induced ischemia‐reperfusion renal and pulmonary injuries and, as a result, on the overall clinical course of the patients. On the other hand, no protection against AKI was offered by N‐acetylcysteine in patients undergoing off‐pump cardiac surgery in this study, as well as in a recent study by Prasad et al 29 It is possible that these results reflect the counteracting action of N‐acetylcysteine on oxidative stress, reperfusion injury, and systemic inflammatory response associated with CPB. Indeed, severe oxidative stress was demonstrated to occur from the extracorporeal circulation of blood, 37 blood cardioplegia, and reperfusion injury 38 .…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…Moreover, in this study, patients treated with N‐acetylcysteine were less likely to require mechanical ventilation for a prolonged (>48 hours) period (3% vs 18%; P < .001) and to have a stay in the intensive care unit of longer than 4 days (13% vs 33%; P < .001), suggesting a positive effect of N‐acetylcysteine on CPB‐induced ischemia‐reperfusion renal and pulmonary injuries and, as a result, on the overall clinical course of the patients. On the other hand, no protection against AKI was offered by N‐acetylcysteine in patients undergoing off‐pump cardiac surgery in this study, as well as in a recent study by Prasad et al 29 It is possible that these results reflect the counteracting action of N‐acetylcysteine on oxidative stress, reperfusion injury, and systemic inflammatory response associated with CPB. Indeed, severe oxidative stress was demonstrated to occur from the extracorporeal circulation of blood, 37 blood cardioplegia, and reperfusion injury 38 .…”
Section: Discussioncontrasting
confidence: 68%
“…Notably, when only patients undergoing cardiac surgery with CPB support were considered (90% of the whole study population), N‐acetylcysteine‐treated patients showed a significantly lower incidence of AKI than controls (40% vs 54%; P = .03). Conversely, no beneficial effect of N‐acetylcysteine on renal function was observed in a recent study by Prasad et al, 29 in which only high‐risk patients undergoing off‐pump CABG were considered.…”
Section: Resultsmentioning
confidence: 92%
“…We conducted a detailed evaluation of the complete report for 236 trials proceeded to a detailed evaluation of the complete report, following which a further 175 articles were excluded. Finally, the 61 remaining articles were included in our meta‐analysis . A flowchart describing the article selection process for this meta‐analysis is shown in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…By far, only one clinical trial has evaluated the effect of NAC on prevention of renal dysfunction after OPCAB, which could not demonstrate any beneficial influence. 19 In that study, however, the dose of NAC was relatively low; 1200 mg a day from preoperative day until the second postoperative day. It was suggested that the effect of NAC as an antioxidant was dose dependent and high dose of NAC could fully demonstrate its effect.…”
Section: Discussionmentioning
confidence: 99%